Higher Abdominal Adiposity Is Associated With Lower Muscle Strength in Chilean Adults - Palacio, Ana Cristina; Díaz-Torrente, Ximena; Quintiliano-Scarpelli, Daiana (Frontiers in Nutrition, 2022)
Handgrip strength (HGS) is a well-established indicator of muscle strength and a reasonable clinical predictor of metabolic health and diseases. This study explores the association between relative muscular strength and abdominal obesity (AO) in healthy Chilean adults. A convenience sample was recruited (n = 976) between 2018 and 2020. The HGS was determined by dynamometry. The anthropometry (weight, height, waist, and mid-arm circumference) and physical activity were also measured. The relative HGS (RHGS) was calculated by dividing the maximum HGS of the dominant hand by the body mass index. The AO was defined as a waist circumference (WC) >88 cm for women, and >102 cm for men. From the sample, 52.6% were women, 56.4% had excessive weight, and 42.7% had AO. The absolute and RHGS were greater in men compared to women (p < 0.001) and were decreased with age in both sexes. We observed a moderate negative correlation between WC and RHGS (rho = −0.54, and rho = −0.53, for men and women, respectively). The RHGS was lower in individuals with AO, independent of age and sex (p < 0.05). For each cm increase in WC, the odds of low RHGS (<25th percentile) increased by 12 and 9% for men and women, respectively. The AO is related to higher odds for low RHGS (OR: 1.72; 95% CI: 1.23–2.41). In our sample of healthy adults, a higher AO was associated with a lower muscle strength measured by dynamometry.